Racial Disparities in Comorbidity and Severe Maternal Morbidity/Mortality in the United States: An Analysis of Temporal Trends. Issue 6 (June 2018) - Metcalfe, Amy; Wick, James; Ronksley, Paul
Abstract : (Abstracted from Acta Obstet Gynecol Scand 2018;97:89–96) Multiple studies have found a temporal increase in the incidence of severe maternal morbidity and mortality in recent years in the United States; for instance, between 1998/1999 and 2008/2009, severe maternal morbidity during delivery hospitalizations increased by 75%. This increase has not been uniform across all demographic groups.